Understanding mathematical concepts using the mind mapping learning model for high school students - Jumri, Rahmat; Faras, Haniyah Raihani; Ramadianti, Winda (Universitas Sarjanawiyata Tamansiswa, 2024)
The purpose of this study is to investigate how the understanding of mathematical concepts by grade XI students at SMA N 6 Bengkulu City is influenced by the application of the mind mapping method. This study employs a quasi-experimental design with control groups. The participants consist of two sections, each with thirty-six students: XI MIPA A and XI MIPA D. The use of mind mapping techniques serves as the independent variable, while students' conceptual knowledge is the dependent variable. Measurements were conducted using tests. Data analysis compared the conceptual knowledge of the experimental and control groups using t-tests and hypothesis tests with a significance level of 5%. The findings indicate that mind mapping positively affects the students' conceptual understanding of mathematical matrices. The conceptual understanding of the experimental group improved significantly, as evidenced by the posttest results, compared to the control group that utilized conventional methods. In conclusion, the mind mapping learning model proves to be an effective tool in enhancing students' comprehension of mathematical concepts.